2012
DOI: 10.3892/mmr.2015.3483
|View full text |Cite
|
Sign up to set email alerts
|

Generation of transgenic fibroblasts producing doxycycline-inducible human interferon-α or erythropoietin for a bovine mammary bioreactor

Abstract: Abstract. Interferon α (IFN-α) is a cytokine, produced predominantly in immune cells in response to pathogens, which interferes with viral replication in host cells. Another cytokine hormone, erythropoietin (EPO), is synthesized in interstitial fibroblasts of the kidney and acts as a stimulator for the production of red blood cells. Importantly, the two cytokines have been used in the treatment of certain hematological malignancies, including renal anemia. In the production of recombinant proteins, a transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A low dose of doxycycline (Dox) regulates the expression of target gene without toxicity to animals or cells. Numerous studies have shown inducible Tet-On system is a convenient tool for reversible and very tightly controlled conditional gene expression in zebrafish, drosophila, murine, porcine and bovine models 23 27 . In our previous study, we successfully used the Tet-On system to induce expression of miR-34c in bovine fibroblasts 28 .…”
Section: Introductionmentioning
confidence: 99%
“…A low dose of doxycycline (Dox) regulates the expression of target gene without toxicity to animals or cells. Numerous studies have shown inducible Tet-On system is a convenient tool for reversible and very tightly controlled conditional gene expression in zebrafish, drosophila, murine, porcine and bovine models 23 27 . In our previous study, we successfully used the Tet-On system to induce expression of miR-34c in bovine fibroblasts 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the mammalian genome architecture with its compartmentalization into various chromatin domains, , cellular regulatory DNA elements such as enhancers, insulators, or silencers and the epigenetic status of a particular chromatin domain can influence the synthetic expression cassettes. Since standard gene transfer methods rely on random integration of transfected DNA, cell clones with tight regulation of the transgenes have to be identified by appropriate selection and sorting strategies. Since screening is limited for the establishment of transgenic mice, the specific targeting of cassettes into predefined chromosomal loci is a favorable strategy for prediction of expression properties in tissues.…”
Section: Introductionmentioning
confidence: 99%